Studies in partial slip contacts applied to fretting fatigue - Thaitirarot, A (2013)
Detailed analysis of all the fretting fatigue test results available in the literature is carried out by employing refined asymptotic solutions. Several different criteria are used and it is shown that two give an improvement over stress-based criteria. These procedures provide a practical method for both designing against fretting fatigue failure and quantifying the nucleation time when fretting is unavoidable. The reduced stiffness method is developed together with the evolutionary algorithm which is the direct implementation of the Signorini and Coulomb friction contact inequalities. This method is capable of solving two dimensional frictional contact problems in significantly less time and is more accurately than a traditional FE approach. In addition, algorithms for determining shakedown limit of coupled contacts have also been developed. A problem of a plane receding contact was considered where a strip is pressed against an elastically similar half-plane by normal pressure extending along the strip surface but stopping short of the end. These phenomena are analysed, together with the behaviour of the system when the pressure is removed. Interfacial characteristics of a lap joint formed using friction grip bolts is also considered as these produce a receding contact. The joints consist of two elastically similar laps pressed in contact by a constant normal force and subject to oscillatory bulk load at the free end of the laps. Bulk load applied at the free ends causes a smooth change in the size of contact and the development of the slip zones. The trend of energy dissipation with the extent of contact and magnitude of remote tension, at various friction coefficients, has been found. Lastly, axisymmetric receding contact between a circular elastic disc pressed against a half-space has been studied. The disc is first subjected to normal pressure followed by torsion. Normal pressure alone causes a contact interface to separate, if the loaded area is sufficiently small. Torsion is subsequently applied which causes a change in the size of contact and has a significant effect on the direction of the resultant slip displacement and the stick/slip boundaries.